Bolivia : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bolivia. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Bolivia has achieved strong economic performance and poverty reduction over the past decade. Real GDP growth has averaged about 5 percent since 2006, and the poverty ratio has declined by 16 percentage points. Real GDP growth is projected to stay relatively strong at 4.1 percent in 2015, despite the sharp decline in oil prices that is starting to have an impact. A sizable public investment budget, strong credit growth to the private sector, and robust private consumption are expected to support activity. Growth is expected to decelerate to 3.5 percent over the medium term, as the full impact of the new commodity price normal is felt.